Preliminary assessment of fentanyl and synthetic opioids prevalence among addiction patients by means of hair analysis - Alberto Salomone; Ermelinda Levari; Andrea Lotti; Marinella Frenguelli; Valentina Longo; Massimo Gottardi; Giovanni Michele Marchio; Martina Stefani; Roberta Ferrucci; Attilio Negri; Ornella Corazza (Elsevier, 2021)
Background: Although the diffusion of novel synthetic opioids has become a worldwide phenomenon, their prevalence of use in Italy seems to be limited. Existing national data is mainly derived by anamnestic surveyslacking of toxicological validation and not always disclosing the use of these compounds, which might remain under-diagnosed. Methods: an assessment of the metabolites of the main synthetic opioids on hair samples was carried out among patients admitted at the Addiction Treatment Unit of Trento. The analytical approach included: (a) screening by means of immunoenzymatic method for fentanyl, fentanyl analogs and oxicodone; (b) confirmation of the samples resulted positive for fentanyl and oxicodone by means of HPLC-MS/; (c) search and dosage detection of Tramadol by means of HPLC-MS/MS. Results: 3 out of 309 analysed samples were found positive: one was positive to Fentanyl and two to 4-ANPP. In the same cohort, 6 samples were also found positive for Oxycodone . Tramadol was searched in 189 samples and 12 of them resulted positive. Discussion and conclusion: Those found positive were mainly young adults engaging in dangerous patterns of use and lacking awareness of risks. The phenomenon requires further consideration by health professionals. Training and more evidence-based information on synthetic opioids as well as other Novel Psychoactive Substances (NPS) are urgently needed.